Cross Sectional and Longitudinal Investigation of Pain Sensitivity in Early Adulthood - Waller, Robert (Curtin University, 2019)
This doctoral thesis investigated pressure and cold pain sensitivity in young adults of the Raine Study. The work confirmed that pressure pain threshold measurement is reliable in large cohort studies. The reference data reported assists the understanding of ‘normal’ pain sensitivity in young adults. Heightened cold pain sensitivity is associated with a “medium” or “high” pain experience in young adults. Early life stress is associated with pain sensitivity at 22-years of age.